Differential Imaging-Based Porous Plate Measurements of Fluid Distribution and Capillary Pressure During Drainage in a Multiscale Oolitic Limestone - Anindityo Patmonoaji; Rukuan Chai; Asli S. Gundogar; Mohamed Regaieg; Martin J. Blunt; Branko Bijeljic (Transport in Porous Media, 2025)
Using a combination of a porous plate, micro-computed tomography, and differential imaging, the differential imaging porous plate (DIPP) method was employed to monitor spatial fluid distribution and measure capillary pressure between oil and water in an oolitic limestone, Ketton. Based on geological interpretation, mercury intrusion capillary pressure (MICP), and scanning electron microscopy (SEM), the pores were classified into macropores, intermediate-size pores, and micropores. Macropores are formed by the intergranular packing of ooid spheres, micropores are found within the intragranular porosity of the ooids, and intermediate-size pores arise from interstitial particles filling the macropores. This multiscale classification was validated by observing the fluid distribution patterns during drainage. A comparison with MICP showed that DIPP tends to yield lower capillary pressure values even after correction for fluid properties, consistent with previous studies on laminated sandstones. The results suggest that porous plate measurements using oil and water provide a more representative characterization of capillary pressure than MICP.